2011
DOI: 10.1002/wea.679
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variations in the nocturnal heat island of London

Abstract: Urban landscapes typically experience higher air temperatures than the surrounding countryside due to absorption of solar heat by the fabric of buildings and trapping of outgoing longwave radiation within enclosed spaces. There is also less evapotranspiration from paved areas compared with vegetated surfaces, leaving a greater fraction of solar energy for surface heating. Artificial heat sources from transport, industry, air conditioning and space heating can further contribute to local warming. Although such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 14 publications
4
46
1
Order By: Relevance
“…Ambiguity concerning the atmospheric conditions depicted in proxy‐based reconstructions is an inherent problem with using the ‘black box’ approach, where a variety of different predictors are incorporated over the length of the series. Owing to the consistent nature of the Paris–London index over time as an indicator of westerly flow, it has been shown that since circa 1970, the summer Paris–London index has remained in an unprecedented negative phase, which is likely due to an increased propensity of blocking episodes, based on the findings of other studies (Casty et al , 2007; Folland et al , 2009; Wilby et al , 2011). Qualitatively, the variability of the summer Paris–London index over the last 200 years bears a close relationship to the variability of summer rainfall (Briffa et al , 2009).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Ambiguity concerning the atmospheric conditions depicted in proxy‐based reconstructions is an inherent problem with using the ‘black box’ approach, where a variety of different predictors are incorporated over the length of the series. Owing to the consistent nature of the Paris–London index over time as an indicator of westerly flow, it has been shown that since circa 1970, the summer Paris–London index has remained in an unprecedented negative phase, which is likely due to an increased propensity of blocking episodes, based on the findings of other studies (Casty et al , 2007; Folland et al , 2009; Wilby et al , 2011). Qualitatively, the variability of the summer Paris–London index over the last 200 years bears a close relationship to the variability of summer rainfall (Briffa et al , 2009).…”
Section: Discussionmentioning
confidence: 82%
“…Further supporting evidence is provided by weather‐type catalogues for the UK. Both, the subjective Lamb Weather‐type index, and the objective Jenkinson‐Collinson classification show a pronounced shift in circa 1970 to many more days in summer classified as anticyclonic (Wilby et al , 2011).…”
Section: Temporal Variations In the Paris–london And Nao Indicesmentioning
confidence: 99%
“…This is because most of these comparisons only consider days that maximise the urban/rural difference and so are not directly relevant in the context of long-term monthly averages for typical (non-city-centre) weather stations. Using the example from London (Wilby et al, 2011) an urbanization effect over decadal timescales is apparent, but this could easily be explained by some periods being dominated by circulation patterns that emphasize an effect while other patterns reduce the effect.…”
Section: Urbanization Effectsmentioning
confidence: 99%
“…There are two major methods used for estimation of the urban contribution to the observed warming trend: “city minus rural” and “observations minus reanalysis” methods. Previous studies showed that the urbanization effect have little effect on warming trends over cities that had been grown for a long time and have always been urban‐like as London, Vienna, Sydney, and Melbourne (Jones & Lister, ; Jones, Lister, & Li, ; Trewin, ; Wilby, Jones, & Lister, ). It was also suggested that globally, urban locations manifested even less warming than rural stations based on satellite data (Hansen et al, ; Wickham et al, ).…”
Section: Introductionmentioning
confidence: 99%